Constance Maynard's Life-Writing Considered as Spiritual Autobiography. Issue 1 (2nd January 2016) - Jay, Elisabeth
Abstract : Viewing Constance Maynard's unwieldy life-writings within the tradition of spiritual autobiography reveals many of the irresolvable tensions with which she wrestled. Although she chose to see her public role as spearheading a crusade against modern rationalism, her inner life was as much concerned with the struggle to repudiate her parents' ascetic Evangelical piety in favour of a more emotionally intense spirituality. Her conviction of conversion's centrality fostered a sense of mission which bolstered a sense of her own exceptionality as a 'prophet' chosen by God. This in turn nourished her belief that she was justified in exempting herself from the roles and relationships conventionally assigned to her gender, by pursuing same-sex desire and sexless motherhood.